Glia cell line-derived neurotrophic factor mediates survival of murine sympathetic precursors - Heermann, Stephan; Mätlik, Kert; Hinz, Ursula; Fey, Jutta; Arumae, Urmas; Krieglstein, Kerstin (Journal of neuroscience research, 2013)
During embryonic development, neurons are first produced in excess, and final numbers are adjusted by apoptosis at later stages. Crucial to this end is the amount of target-derived growth factor available for the neurons. By this means, the target size correctly matches the innervating neuron number. This target-derived survival has been well studied for sympathetic neurons, and nerve growth factor (NGF) was identified to be the crucial factor for maintaining sympathetic neurons at late embryonic and early postnatal stages, with a virtual complete loss of sympathetic neurons in NGF knockout (KO) mice. This indicates that all sympathetic neurons are dependent on NGF. However, also different glia cell line-derived neurotrophic factor (GDNF) KO mice consistently presented a loss of sympathetic neurons. This was the rationale for investigating the role of GDNF for sympathetic precursor/neuron survival. Here we show that GDNF is capable of promoting survival of 30% sympathetic precursors dissociated at E13. This is in line with data from GDNF KOs in which a comparable sympathetic neuron loss was observed at late embryonic stages, although the onset of the phenotype was unclear. We further present data showing that GDNF ligand and canonical receptors are expressed in sympathetic neurons especially at embryonic stages, raising the possibility of an autocrine/paracrine GDNF action. Finally, we show that GDNF also maintained neonatal sympathetic neurons (40%) cultured for 2 days. However, the GDNF responsiveness was lost at 5 days in vitro. © 2013 Wiley Periodicals, Inc.